Profil Pemetaan Keterampilan Berpikir Kritis Siswa pada Materi Ekologi dan Keanekaragaman Hayati - Radeswandri; Khairunnissa Arrumi; Berlian, Mery; Vebrianto , Rian (Milenial: Journal for Teachers and Learning, 2024)
Critical thinking skills are the ability to engage in a specific activity, process, or procedure. This study aims to measure students' critical thinking skills in ecology and biodiversity. The method used in this study is a survey. Based on the survey results, it is known that the number of test items is 10 items distributed into 6 indicators. The number of research subjects is 35 students from junior high school level and consists of several ethnic groups such as Malay, Batak, Minang, and Sundanese. Based on the assessment of students' critical thinking skills in ecology and biodiversity, the average percentage of critical thinking skills reached 82.29%. With a percentage of 82.29%, it can be concluded that the majority of students are able to perform well in these aspects, thus categorized as "Very Good". This indicates a positive achievement in learning ecology and biodiversity.